Ground- and excited-state characteristics in photovoltaic polymer N2200. Issue 33 (14th June 2021) - Wen, Guanzhao; Zou, Xianshao; Hu, Rong; Peng, Jun; Chen, Zhifeng; He, Xiaochuan; Dong, Geng; Zhang, Wei
Abstract : Ground- and excited-states properties of N2200 have been studied by steady-state and time-resolved spectroscopies as well as time-dependent density functional theory calculations. Abstract : As a classical polymer acceptor material, N2200 has received extensive attention and research in the field of polymer solar cells (PSCs). However, the intrinsic properties of ground- and excited-states in N2200, which are critical for the application of N2200 in PSCs, remain poorly understood. In this work, the ground- and excited-state properties of N2200 solution and film were studied by steady-state and time-resolved spectroscopies as well as time-dependent density functional theory (TD-DFT) calculations. The transition mechanism of absorption peaks of N2200 was evaluated through the natural transition orbitals (NTOs) and hole–electron population analysis by TD-DFT. Time-resolved photoluminescence (TRPL) study shows that the lifetimes of singlet excitons in N2200 chlorobenzene solution and film are ∼90 ps and ∼60 ps, respectively. Considering the absolute quantum yield of N2200 film, we deduce that the intrinsic lifetime of singlet exciton can be as long as ∼20 ns. By comparing the TRPL and transient absorption (TA) kinetics, we find that the decay of singlet excitons in N2200 solution is dominated by a fast non-radiative decay process, and the component induced by intersystem crossing is less than 5%. Besides that, the annihilation radius, annihilation rate and diffusion length of singlet excitons in N2200 film were evaluated as 3.6 nm, 2.5 × 10 −9 cm 3 s −1 and 4.5 nm, respectively. Our work provides comprehensive information on the excited states of N2200, which is helpful for the application of N2200 in all-PSCs.